BAHASA SEBAGAI OBJEK KAJIAN GENDER - Krishna Adnyani, Kadek Eva (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2014)
The qualitative research is aimed at describing language as an object of gender studies pioneered by Robin Lakoff. The data of the research were the special words and grammar which exclusively referred to be used by women and used as an object of gender studies. The findings show that one can often identify the values of society from the language used because language is a reflection of the society. The differences between the competitive assertive male style and cooperative supportive female style tend to dominate the studies conclusions about relations between gender and language. However, this should be considered with caution since language use also varies according to situational conditions.Keywords: language, gender, relation.